RISK FACTORS AND CHARACTERISTICS AND EFFECTS OF LOW BIRTH WEIGHT PREVENTION PROGRAMS - Grbić, Dragana (Medicinski podmladak, 2024)
The World Health Organization had set the goal of a 30% reduction in the number of infants born with a weight lower than 2500 g by the year 2025 as part of the Global Nutrition Targets. This mini-review aims to present the risk factors and characteristics, effects and challenges of preventive programs aimed at reducing the prevalence of low birth weight (LBW). Preventive programs are of particular importance due to the growing incidence of risk factors in low-income countries. Risk factors associated with LBW, including the risks for premature birth and intrauterine fetal growth restriction, can be divided into health, nutritional, social and sanitary-hygienic factors and associated factors. Preventive programs and interventions aimed to reduce the rate of LBW (including premature birth and intrauterine fetal growth restriction) and reduce the incidence of risk factors that lead to LBW. The greatest effect on the rate and risk reduction for LBW had multiple micronutrients and balanced protein-energy nutrition supplementation programs, programs to quit smoking and use alcoholic beverages during pregnancy, programs to strengthen the quality of antenatal health care and pregnancy infection prevention programs. Interventions of psychosocial support for pregnant women have had a positive effect as part of other activities for more effectively reaching the global goals for the LBW reduction prevalence. The biggest challenges of preventive programs to LBW reduction are poverty, illiteracy, unemployment and lack of social protection. Multi-causality and complexity of LBW, as well as the numerous risks that affect this adverse pregnancy outcome, make it difficult to implement preventive programs that will lead to a significant reduction in prevalence in a shorter period. Recognizing the role of women in society and strengthening social and health protection in comprehensive preventive programs has a perspective for LBW rate reduction, as well as improving the reproductive health of women as a whole.